2016
DOI: 10.5545/sv-jme.2015.2901
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Process Parameters on Part Wall Thickness Variation in Conventional Metal Spinning of Cr-Mn Austenitic Stainless Steels

Abstract: Metal spinning is one of a number of flexible sheet forming processes which is a cost effective option for the production of parts with a very

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
(29 reference statements)
1
0
0
2
Order By: Relevance
“…Percentage wall thickness variation from the original blank thickness, springback in the radial direction, surface roughness, and roundness error have been evaluated for produced cups, Table 2. Reported thickness variation values go in agreement with those obtained by Šugár et al [19]. Springback values are in the accepted range reported by Essa and Hartley [20].…”
Section: Test Runs Of the Retrofitted Systemsupporting
confidence: 91%
“…Percentage wall thickness variation from the original blank thickness, springback in the radial direction, surface roughness, and roundness error have been evaluated for produced cups, Table 2. Reported thickness variation values go in agreement with those obtained by Šugár et al [19]. Springback values are in the accepted range reported by Essa and Hartley [20].…”
Section: Test Runs Of the Retrofitted Systemsupporting
confidence: 91%
“…Hence, the application of concave tool path has a negative effect on the height of the spun part from the technological point of view, since in the previous research [32] was observed that concave tpp causes the most massive thickness reduction in the wall zone of the spun cups. This conclusion is also confirmed by research of Šugár [33]. Overall it can be concluded, that linear tool path profile along with the application of tool feed of 0.8 mm leads to the optimal values of the spun part wall heights.…”
Section: Fig 3 Spun Part Wall Heights For Convex Tool Path Profilesupporting
confidence: 68%
“…[9] sıvama parametrelerinin kalınlığa olan etkileri incelemek için, 1 mm kalınlığında Al 1060 malzemeyi konik sıvamışlardır. İş parçası cidar kalınlığının, mandrel devir hızı ve ilerleme hızı arttıkça azaldığını [10,11] deneysel ve sayısal olarak göstermişlerdir.…”
Section: Gi̇ri̇ş (Introduction)unclassified
“…Sin α =1xsin 60° = 0,86 mm(10) Yapılan hesaba göre analiz sürecinde iş parçasının plastik deformasyon sonrası kalınlığı 0,86 mm'dir. Bu değer akma sınırının başladığı en büyük noktayı ifade etmektedir.…”
unclassified